Perbandingan Nilai Pendapatan Secara Ekonomi Integrasi Padi Ikan (Minapadi) dan Non (Minapadi) di Kedah Malaysia - Nabila, Rezya; Harahap, Mailina; Rahim, Hairazi; Br Kabeakan, Trisna Mei (JURNAL AGROPLASMA, 2024)
Government agricultural policies around the world prioritize increasing production, productivity, and sustainability in cities and countries while addressing food security and resource constraints. One promising strategy that is gaining global attention is integrating rice and fish cultivation (Mina padi), into a sustainable agriculture framework. This approach offers ecological and economic benefits, such as increased soil fertility, natural pest control, and increased income. Apart from that, it can also be a form of agrotourism in various cities and countries. The catfish farming sector has experienced major growth and made a significant contribution to aquaculture production. To optimize agricultural space and increase income, efforts are being made to integrate rice cultivation with catfish cultivation. This study aims to evaluate the monetary benefits of such integration. One way to optimize the potential of technically irrigated rice fields while increasing farmers' income is through engineering appropriate technology for rice fields. The recommended technological engineering is through a cultivation system by raising fish with rice in rice fields or also called minapadi. This study aims to evaluate the monetary benefits of such integration. This research, which was conducted in the Jitra PPA area in Kedah, used an experimental research methodology that focused on two scenarios involving rice production using a floating bed system. This innovative approach avoids conventional chemicals to reduce harm to aquatic life, especially catfish. This research produced 2 situations that estimated rice production at 3,624 kg per hectare, and a second situation that estimated rice production at 8,872 kg per hectare, both of which were integrated with catfish cultivation. A partial budgeting approach was used to assess the financial feasibility of this integrated system, by examining changes in net income based on total revenues and total costs. Keywords: rice, catfish, income